Landscape development for Mr. and Mrs. Henry Mancini [drawings A - G] - Arthur G. Barton::::::::: (1978)
Drawings A-G: A) multi-trunk tree staking; B) tree planting and staking; C) shrub planting detail; D) ground cover planting; E) espalier and training detail; F) sprinkler controller; and G) remote control valve